Pengaruh Budaya Kerja Dan Stres Kerja Terhadap Loyalitas Karyawan Yang Dimediasi Kompensasi Divisi Quality Control PT. Mitsubishi Motors Krama Yudha Indonesia - Tririsqi, Desi; Suwandi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
functions as a driving factor for every activity within the company. As the number of human resources currently available increases, special selection is needed in order to obtain the best resources that suit the desired needs. The aim of the research is to analyze and determine the influence of work culture and work stress on employee loyalty which is mediated by compensation from the Quality Control Division of PT. Mitsubishi Motors Krama Yudha Indonesia Using data collection techniques in the form of questionnaires and direct observation with a total of 56 respondents. The application used for data processing is SmartPLS Version 3.0. The findings in the research state that work culture has significant results on employee loyalty after being mediated by innovative compensation.